Administration of ivermectin to peridomestic cattle: a promising approach to target the residual transmission of human malaria. (December 2015) - Pooda, Hermann; Rayaisse, Jean-Baptiste; Hien, Domonbabele; Lefèvre, Thierry; Yerbanga, Serge; Bengaly, Zakaria; Dabiré, Roch; Belem, Adrien; Sidibé, Issa; Solano, Philippe; Mouline, Karine
Abstract Background The success of current control tools in combatting malaria vectors is well established. However, sustained residual transmission ofPlasmodium parasites persists. Mass drug administration (MDA) to humans of the endectocide ivermectin for vector control is receiving increasing attention. However, vectors feeding upon animals escape this promising approach. Zoophagy of mosquitoes sustains both the vector population and endemic population of vector-borne pathogens. Therefore, only a strategy that will combine ivermectin MDAs targeted at humans and their peridomestic animals could be successful at controlling residual malaria transmission. Methods Burkinabé cattle have been treated with injectable therapeutic dose of ivermectin (0.2 mg/kg of body weight) to render blood meals toxic to field representative populations ofAnopheles coluzzii carrying thekdr mutation. Direct skin-feeding assays were performed from 2 to 28 days after injection (DAI) and mosquitoes were followed for their survival, ability to become gravid and fecundity. Membrane feeding assays were further performed to test if an ivermectin blood meal taken at 28 DAI impacts gametocyte establishment and development in females fed with infectious blood. Results The mosquitocidal effect of ivermectin is complete for 2 weeks after injection, whether 12 days cumulative mortalities were of 75 and 45 % the third and fourth weeks, respectively. The third week, a second ivermectin blood meal at sub-lethal concentrations further increased mortality to 100 %. Sub-lethal concentrations of ivermectin also significantly decreased egg production by surviving females, increasing further the detrimental effect of the drug on vector densities. Although females fitness was impaired by sub-lethal ivermectin blood meals, these did not diminish nor increase their susceptibility to infection. Conclusion This study demonstrates the potential of integrated MDA of ivermectin to both human and peridomestic cattle to target vector reservoirs of residual malaria transmission. Such integration lies in 'One-Health' efforts being implemented around the globe, and would be especially relevant in rural communities in Africa where humans are also at risk of common zoonotic diseases.